KONSELING PRANIKAH SEBAGAI UPAYA PREVENTIF DAN ANTISIPASI PERCERAIAN DALAM PERNIKAHAN DINI - Heri Fadli Wahyudi; Annatul Aini (Bayan lin-Naas : Jurnal Dakwah Islam, 2022)
ABSTRACT: Every human must have a dream of having a happy family. A happy god-endowed family, in contrast to the things damned by God, is a divorce between the two domestic partners. In this case, the researcher is very interested in a problem that often occurs in society: divorce. Divorce is rife in early marriages or marriages performed by a pair of underage humans. Early marriage is a marriage that is carried out in adolescence or a transition period and is not old enough or not ready to marry The Marriage Law Number 1 of 1974 sets the age limit for sacred marriage, namely a 19-year-old man and a 16-year-old woman. From the researcher's initial observation that in Saronggi village there were many Early Marriage Divorces, researchers were interested in making observations in Saronggi Village. In this case, researchers also use a Qualitative (field) Case Study approach so that more data can be obtained from researchers about the occurrence of Early Marriage Divorce in KUA Saronggi. This study aimed to find out which strategy was used by KAU Saronggi extension workers to anticipate a Marriage Divorce for Brides Who Marry Early. The results of this study are; First, the implementation of cognitive counseling as a preventive measure against divorce from both partners. Second, mental counseling to waiting is a curative effort toward the thinking patterns of both partners.